2022
DOI: 10.1111/aas.14158
|View full text |Cite
|
Sign up to set email alerts
|

Continuous wireless pre‐ and postoperative vital sign monitoring reveal new, severe desaturations after vascular surgery

Abstract: Objectives Postoperative deviating physiologic values (vital signs) may represent postoperative stress or emerging complications. But they can also reflect chronic preoperative values. Distinguishing between the two circumstances may influence the utility of using vital signs in patient monitoring. Thus, we aimed to describe the occurrence of vital sign deviations before and after major vascular surgery, hypothesising that preoperative vital sign deviations were longer in duration postoperatively. Methods In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…This study was registered on clinicaltrials.gov as NCT05347784. The study cohort consisted of patients from three surgical studies in the Wireless Assessment of Respiratory and circulatory Distress (WARD) project(NCT03491137, NCT04473001 and NCT04628858) after approval from the science ethics committee for the capital region of Denmark (H-17033535, H-20002220 and H-19086583) [16,20,21] all studies adhered to the Helsinki Declaration.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was registered on clinicaltrials.gov as NCT05347784. The study cohort consisted of patients from three surgical studies in the Wireless Assessment of Respiratory and circulatory Distress (WARD) project(NCT03491137, NCT04473001 and NCT04628858) after approval from the science ethics committee for the capital region of Denmark (H-17033535, H-20002220 and H-19086583) [16,20,21] all studies adhered to the Helsinki Declaration.…”
Section: Patient Populationmentioning
confidence: 99%
“…Ethics approval and consent to participate study cohort consisted of patients from three surgical studies in the Wireless Assessment of Respiratory and circulatory Distress (WARD) project(NCT03491137, NCT04473001 and NCT04628858) which were given approval from the local science ethics committee(H-17033535, H-20002220 and H-19086583)[16,20,21]. Informed consent was collected prior to study initiation on all participants.…”
mentioning
confidence: 99%
“…The case of atrial fibrillation also supports that development of CVSM systems must consider any preexisting conditions as to reduce alerts caused by an abnormal but chronic condition, whilst identifying new important deviations in the same patient. Thus, a study of vascular patients showed that minor deviations may be explained by preoperative chronic conditions whereas severe deviations are not present preoperatively and as such cannot be dismissed as a chronic condition even in this highly comorbid population [17].…”
Section: Use Of Continuous Systems In Postoperative Carementioning
confidence: 99%